2022
DOI: 10.4103/jmas.jmas_244_20
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery in India during the COVID-19 pandemic

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has posed an unprecedented challenge to the healthcare systems worldwide. This uncharted territory has changed the practices in modern healthcare delivery; this is particularly true in the case of minimally invasive surgery (MIS) where various changes are being adopted. This survey was conducted to determine the impact of the pandemic and the changes being adopted in the field of MIS, from a resource-limited developing country, India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, studies have demonstrated that the pandemic and the policy responses to it have reduced surgical volumes, particularly for elective procedures. 79 , 80 , 81 Post-operative mortality rates were also higher in COVID-19 patients, thereby increasing overall POMR. 82 More broadly, there have been increases in the delay to care, 83 unemployment, 84 and poverty.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies have demonstrated that the pandemic and the policy responses to it have reduced surgical volumes, particularly for elective procedures. 79 , 80 , 81 Post-operative mortality rates were also higher in COVID-19 patients, thereby increasing overall POMR. 82 More broadly, there have been increases in the delay to care, 83 unemployment, 84 and poverty.…”
Section: Discussionmentioning
confidence: 98%